Evaluating Arabidopsis thaliana ubiquitin1 promoter activity in Solanum lycopersicum - Gossens, Richard (Student Undergraduate Research E-journal!, 2016)
Overexpression of genes involved in heat stress response may yield heat stress resistant plants. To bring genes into overexpression, a good constitutive promoter is key. The key question of this study was: Is the Arabidopsis thaliana ubiquitin1 promoter constitutively active in Solanum lycopersicum? S. lycopersicum plants where transformed with an A. thaliana ubiquitin1 promoter driving expression of β-glucuronidase (GUS). Six out of the ten successfully transformed explants showed expression of GUS, either in protein activity or transcript. The research shows that the A. thaliana ubiquitin1 promoter is not constitutively active in S. lycopersicum, but instead shows sporadic expression.